1987
DOI: 10.1016/0035-9203(87)90148-9
|View full text |Cite
|
Sign up to set email alerts
|

Serological evidence of Hantaan-related viruses in Hong Kong

Abstract: Sera from rats (Rattus norvegicus), domestic animals and man in Hong Kong were studied by immunofluorescent antibody assay and plaque reduction neutralization tests for evidence of infection by Hantaan-related viruses. Antibody probably arising from infection by Seoul or a Seoul-like virus was detected in rat and human sera (and one pig serum), highlighting the potential public health importance of this group of viruses in Hong Kong, and in the region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…In 1985, four SEOV isolations were made from urban rats in Hong Kong (strains R 85/14, 19, 35, and 40) [39]. Rat-associated hantavirus infection in both rat and human sera in Hong Kong was subsequently confirmed by IFA and PRNT [40], and two HFRS cases were serologically confirmed ([26], pp. 804 and 807).…”
Section: Overview Of Chronological Seov Findings By Continentmentioning
confidence: 99%
“…In 1985, four SEOV isolations were made from urban rats in Hong Kong (strains R 85/14, 19, 35, and 40) [39]. Rat-associated hantavirus infection in both rat and human sera in Hong Kong was subsequently confirmed by IFA and PRNT [40], and two HFRS cases were serologically confirmed ([26], pp. 804 and 807).…”
Section: Overview Of Chronological Seov Findings By Continentmentioning
confidence: 99%
“…Clinical cases of HFRS have also been reported in other countries and districts in Asia [31][32][33][34][35][36] (Table 1). Serological investigation indicated that there were strong evidences of hantaviral infections in humans in Israeli, Kuwait, Laos, Malaysia, Philippines, Viet Nam and the China Hong Kong Special Administrative Region [37][38][39][40][41][42]. Hantaviral infection was also demonstrated in rodents in Cambodia, though there has been no report of human infections [43] (Table 1).…”
Section: Asiamentioning
confidence: 99%
“…[34][35][36] In surveys of studies from regions where the HTN and SEO viruses, but not PUU virus, occur endemically, antibodies to hantavirus has been reported in samples from small and mediumsized wild mammals such as moles, weasels, hares, foxes, roes, and also among domestic animals such as cats, dogs, and pigs. [37][38][39][40][41][42] Furthermore, in an outbreak of HFRS among laboratory staff, IFA reactions of low titer towards HTN virus were found in rabbits, guinea pigs, dogs, and cats. 43 In line with those studies on the HTN/SEO virus group, [37][38][39][40][41][42][43] the present data may reflect a more general susceptibility to hantavirus infection among mammals.…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39][40][41][42] Furthermore, in an outbreak of HFRS among laboratory staff, IFA reactions of low titer towards HTN virus were found in rabbits, guinea pigs, dogs, and cats. 43 In line with those studies on the HTN/SEO virus group, [37][38][39][40][41][42][43] the present data may reflect a more general susceptibility to hantavirus infection among mammals. Obviously, such susceptibility does not necessarily imply that the infection rate should be high.…”
Section: Discussionmentioning
confidence: 99%